2012
DOI: 10.1186/1746-160x-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical case-study describing the use of skin-perichondrium-cartilage graft from the auricular concha to cover large defects of the nose

Abstract: BackgroundThe composite graft from the conchal cartilage is a graft that is often used, especially in surgery on the nose, due to its capacity to resolve problems of cover and tissue deficit, arising from the removal of neoplasms or as the result of trauma, burns or following over-aggressive rhinoplasty. We have started to use skin-perichondrium-cartilage graft from the ear to cover large areas of the nose with very satisfying results as well as we describe in the reported clinical case.MethodsThe operation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…It is therefore not possible to determine if patients experienced less or more postoperative pain with this approach compared to other techniques. There were no cases of chondritis/ perichondritis, consistent with the literature reports of safe harvesting of cartilage and perichondrium from the concha [ 7 - 10 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is therefore not possible to determine if patients experienced less or more postoperative pain with this approach compared to other techniques. There were no cases of chondritis/ perichondritis, consistent with the literature reports of safe harvesting of cartilage and perichondrium from the concha [ 7 - 10 ].…”
Section: Discussionsupporting
confidence: 88%
“…The modern and sophisticated techniques of GBR involve the use of grafting materials in order to restore anatomy and physiology of the areas with bone decrement 26 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has reported satisfactory results for nasal reconstruction using a large postauricular composite graft (larger than 2.0 cm). Inchingolo et al 17 reported the use of a skin-perichondrium-cartilage graft to cover large nasal defects in a 74-year-old patient; however, the transplanted graft showed severe skin contraction, and there was disfiguration of the nasal dorsum. In these cases, the skin-fat-fascia composite grafts survived without dermal fibrosis or skin contraction, and the epidermal appendages were spared.…”
Section: Discussionmentioning
confidence: 99%